2000
DOI: 10.1007/s005860050224
|View full text |Cite
|
Sign up to set email alerts
|

Outcome scores in degenerative cervical disc surgery

Abstract: Forty-six consecutive patients with neck pain and arm radiculopathy were treated with anterior cervical discectomy and fusion. All patients had neurological symptoms corresponding to a herniated disc and/or spondylosis at one or two cervical levels, verified by magnetic resonance imaging. The patients were stabilized with an anterior graft and randomized to either fixation with a CSLP plate or no internal fixation. Preoperatively and 2 years postoperatively the patients filled in a questionnaire that included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 17 publications
4
45
0
3
Order By: Relevance
“…There are many retrospective reports on positive long-term effects of ACDF such as decreased pain, regression of neurological symptoms, and high rates of a satisfactory global outcome [2,7,9,10,14]. The present results are more modest and more in line with earlier prospective reports, confirming that retrospective studies have a tendency to overestimates outcomes [11,17,19,21,22,30].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…There are many retrospective reports on positive long-term effects of ACDF such as decreased pain, regression of neurological symptoms, and high rates of a satisfactory global outcome [2,7,9,10,14]. The present results are more modest and more in line with earlier prospective reports, confirming that retrospective studies have a tendency to overestimates outcomes [11,17,19,21,22,30].…”
Section: Discussionsupporting
confidence: 86%
“…In the combined total material, 61% of patients reported complete relief of problems or were much better, and 80% were satisfied with the results of surgery, which is in line with other global long-term results [9,10]. Interestingly, Zoe¨ga et al [30] reported that 81% of patients were satisfied with the results after one-level ACDF, despite no apparent improvement in pain or function. This is somewhat in agreement with our study, and verifies previous results showing that outcome is influenced by the method by which it is measured [11], and the relative nature of many outcome variables.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although several reports support this approach as effective [5,6,13], studies using patient-centered functional outcome measures [17,21,26,27,31,35,37] have shown poorer effectiveness, with substantial levels of residual symptoms (deficit) in subjective and objective evaluations [28][29][30]. Peolsson et al [28] found that approximately one third of their study patients had lingering disabilities in objective variables such as strength and range of motion 1 year after ACDF with a cervical intervertebral fusion cage (CIFC).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of that, about 20 % of patients are not completely satisfi ed with the postoperative overall results (11,12) because of persisting diffi culties.…”
mentioning
confidence: 99%